Climate-Induced migration and unemployment in middle-income Africa. (November 2020) - Mueller, Valerie; Gray, Clark; Hopping, Douglas
Highlights: Climate effects on migration are estimated for 3 countries over a 22 years. Mobility declines when temperature increases in Botswana. Precipitation increases reduce (augment) migration in Botswana and Kenya (Zambia). Migratory responses correspond with how local employment varies with climate. Abstract: One of the major unresolved questions in the study of vulnerability to climate change is how human migration will respond in low and middle-income countries. The present study directly addresses this lacuna by using census data on migration from 4 million individuals from three middle-income African countries over a 22-year period. We link these individuals to climate exposures in their origins and estimate climatic effects on migration using a fixed-effects regression model. We show that climate anomalies affect mobility in all three countries. Specifically, mobility declines by 19% with a 1-standard deviation increase in temperature in Botswana. Equivalent changes in precipitation cause declines in migration in Botswana (11%) and Kenya (10%), and increases in migration in Zambia (24%). The mechanisms underlying these effects appear to differ by country. Negative associations between precipitation anomalies, unemployment, and inactivity suggest migration declines may be due to an increased local demand for workers to offset production risk, while migration increases may be indicative of new opportunities in destinations. These country-specific findings highlight the contextually-specific nature of climate-migration relationships, and do not support claims that climate change is widely contributing to urbanization across Africa.